Effect of aquaporin 3 knockdown by RNA interference on antrum formation in sheep secondary follicles cultured in vitro. Issue 5 (5th October 2018) - Paz, Marcela Pinheiro; de Sousa, Francisca Geovania Canafístula; Alves, Benner Geraldo; Lobo, Carlos Henrique; Sales, Antonia Débora; Tavares, Kaio Cesar Simiano; de Sá, Naíza Arcângela Ribeiro; Guerreiro, Denise Damasceno; Maside, Carolina; Rocha, Rebeca Magalhães Pedrosa; Bertolini, Luciana Relly; Bordignon, Vilceu; et al.
Summary: The objectives were to develop an effective protocol for transfection of ovine secondary follicles and to assess the effect of attenuating aquaporin 3 (AQP3) using a small interfering RNA (siRNA-AQP3) on antrum formation and follicular growth in vitro . Various combinations of Lipofectamine® volumes (0.5, 0.75 or 1.0 µl), fluorescent oligonucleotide (BLOCK-iT ™) concentrations (3.18, 27.12 or 36.16 nM) and exposure times (12, 14, 16, 18 or 20 h) were tested. The BLOCK-iT™ was replaced by siRNA-AQP3 in the transfection complex. Ovine secondary follicles were isolated and cultured in vitro for 6 days using standard protocols. Follicles were transfected on day 0 or 3 or on both days (0 and 3) and then cultured for an additional 3 or 6 days. As revealed by the fluorescence signal, the Lipofectamine®/BLOCK-iT™ complex (0.75 µl + 27.12 nM by 12 h of incubation) crossed the basement membrane and granulosa cell and reached the oocytes. In general, the rate of intact follicles was higher and the rate of antrum formation was lower in transfected follicles compared with control follicles. In conclusion, ovine secondary follicles can be successfully transfected during in vitro culture, and siRNA-mediated attenuation of AQP3 gene reduced antrum formation of secondary follicles.